Ethical Programs: Hospitality and the Rhetorics of Software - Brown, James (Digital Humanities, 2015)
Living in a networked world means never really getting to decide in any thoroughgoing way who or what enters your "space" (your laptop, your iPhone, your thermostat . . . your home). With this as a basic frame-of-reference, James J. Brown's Ethical Programs examines and explores the rhetorical potential and problems of a hospitality ethos suited to a new era of hosts and guests. Brown reads a range of computational strategies and actors, from the general principles underwriting the Transmission Control Protocol (TCP), which determines how packets of information can travel through the internet, to the Obama election campaign's use of the power of protocols to reach voters, harvest their data, incentivize and, ultimately, shape their participation in the campaign. In demonstrating the kind of rhetorical spaces networked software establishes and the access it permits, prevents, and molds, Brown makes a significant contribution to the emergent discourse of software studies as a major component of efforts in broad fields including media studies, rhetorical studies, and cultural studies.